Measures to Stabilize National Policy and Relations in Uzbekistan (On the Example of 1989-1997) - OO, Bozorov (European Journal of Life Safety and Stability (2660-9630), 2021)
The article examines the consequences of Soviet national policy in Uzbekistan in the late 80s and 90s of the XX century and measures to eliminate them. It also analyzes the measures taken by the Uzbek government to stabilize national relations, the essence of the new national policy in various aspects.